THE LEADERSHIP MANAGEMENT OF SCHOOL PRINCIPLES IN IMPROVING THE COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Cucu Nurjanah; E. Mulyasa; Wiwik Dyah Aryani (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the planning, implementation, and evaluation of school leadership in improving teacher competence PAI.Penelitian This research is carried out using a qualitative descriptive research approach. The subject is the principal of the school. The informants were vice principals and teachers. Data collection techniques using observation techniques, interviews and documentation. The collected data is checked for data validity, using triangulation, with verification and checking of the adequacy of references. The data analysis technique uses an interactive model. The results showed that (1) Principal leadership planning in improving the competence of PAI teachers includes: (a) Planning based on the vision, mission, school goals, and needs (needsassessment); (b) Involving all elements of the school's academic community; (c) Recruiting new GTT teachers and conducting job position analysis; (d) conducted in work meetings. (2) The implementation of the principal's leadership in improving the competence of PAI teachers includes: (a) Participating in training, seminars, and workshops; (b) Further studies; (c) MGMP revitalization; (e) Improving teacher welfare; (f) Addition of supporting facilities; and (g) teacher certification. As for (3) evaluations carried out by school principals in improving the competence of PAI teachers include: (a) supervising, both personally and in groups; (b) The technique used is direct (directivedirective) and indirect ().non- directive); (c) Aspects of assessment in supervision are teacher presentation, performance teachers in schools, student development, lesson plans, and syllabus.Keywords: Management Leadership, Teachers’ Competency, Islamic Education